Hypospadias in Buffalo (Bubalus Bubalis) Mediterranean Breed - Case Report - Volpato, Rodrigo; Araujo, Michelle S.; Vexenate, Stephane C.O.R.; Oba, Eunice (Journal of Buffalo Science, 2013)
Hypospadias is a rare congenital condition characterized by abnormal development of the penile urethra, penis, scrotum and prepuce. The etiopathogenesis is still not fully elucidated, but it is based on a deficiency of testosterone during the critical stage of morphogenesis. At UNESP’s experimental farm was born a Mediterranean breed buffalo calf with congenital abnormalities in the reproductive system, being diagnosed with hypospadias